Pengembangan Game Edukasi Berbasis Android sebagai Media Pembelajaran Berorientasi pada Kemampuan Berpikir Kritis - Syamsi Damarjati; Asih Miatun (Universitas Muria Kudus, 2021)
This study aimed to develop a valid and practical learning media in terms of theory and practice. The learning media expected to be effective to improve students critical thinking ability in linear program of two-variable material. This study uses the Research and Development (R and D) method starting from potential and problem discovery, data collection, product design, design validation, design revision, limited trial, product revision, wider trial, product revision and mass production. However, due to time constrains this research was only carried out until a wilder trial stage. The subjectin this research were students of class X AV in SMK N 39 Jakarta. The data analysis in this study is qualitative descriptive analysis. The results showed that the educational game